Anxiety enhances pain in a model of osteoarthritis and is associated with altered endogenous opioid function and reduced opioid analgesia. (3rd November 2021) - Lillywhite, Amanda; Woodhams, Stephen G.; Gonçalves, Sara V.; Watson, David J.G.; Li, Li; Burston, James J.; Gowler, Peter R.W.; Canals, Meritxell; Walsh, David A.; Hathway, Gareth J.; Chapman, Victoria
Abstract : Supplemental Digital Content is Available in the Text. Comorbid anxiety and osteoarthritis pain is associated with increased opioid intake. Our translational model identifies reduced opioid analgesia and endogenous opioid dysfunction as potential mechanisms. Abstract: Introduction: Negative affect, including anxiety and depression, is prevalent in chronic pain states such as osteoarthritis (OA) and associated with greater use of opioid analgesics, potentially contributing to present and future opioid crises. Objectives: We tested the hypothesis that the interaction between anxiety, chronic pain, and opioid use results from altered endogenous opioid function. Methods: A genetic model of negative affect, the Wistar–Kyoto (WKY) rat, was combined with intra-articular injection of monosodium iodoacetate (MIA; 1 mg) to mimic clinical presentation. Effects of systemic morphine (0.5–3.5 mg·kg −1 ) on pain behaviour and spinal nociceptive neuronal activity were compared in WKY and normo-anxiety Wistar rats 3 weeks after MIA injection. Endogenous opioid function was probed by the blockade of opioid receptors (0.1–1 mg·kg −1 systemic naloxone), quantification of plasma β-endorphin, and expression and phosphorylation of spinal mu-opioid receptor (MOR). Results: Monosodium iodoacetate–treated WKY rats had enhanced OA-like pain, blunted morphine-induced analgesia, and greater mechanical hypersensitivity following systemic naloxone, compared with Wistar rats, and elevated plasma β-endorphin levels compared with saline-treated WKY controls. Increased MOR phosphorylation at the master site (serine residue 375) in the spinal cord dorsal horn of WKY rats with OA-like pain ( P = 0.0312) indicated greater MOR desensitization. Conclusions: Reduced clinical analgesic efficacy of morphine was recapitulated in a model of high anxiety and OA-like pain, in which endogenous opioid tone was altered, and MOR function attenuated, in the absence of previous exogenous opioid ligand exposure. These findings shed new light on the mechanisms underlying the increased opioid analgesic use in high anxiety patients with chronic pain.